Monitoring hemodynamic changes in stroke-affected muscles using near-infrared spectroscopy. (29th October 2015) - MasoudiMotlagh, Mohammad; Sugar, Jeffrey J; Azimipour, Mehdi; Linz, Whitney W; Michalak, Gregory; Seo, Na Jin; Ranji, Mahsa
The oxygenation level of a tissue is an important marker of the health of the tissue and has a direct effect on performance. It has been shown that the blood flow to the paretic muscles of hemiparetic post-stroke patients is significantly reduced compared to non-paretic muscles. It is hypothesized that hemodynamic activity in paretic muscles is suppressed as compared to non-paretic muscles, and that oximetry can be used to measure this disparity in real-time. In order to test this hypothesis, a custom-made oximetry device was used to measure hemodynamic activity in the forearm extensor muscles in post-stroke patients' paretic and non-paretic sides and in a control population during three exercise levels calibrated to the subject's maximum effort. The change in oxygenation (Δ Oxy ) and blood volume (Δ BV ) were calculated and displayed in real-time. Results show no apparent difference in either Δ Oxy or Δ BV between control subjects' dominant and non-dominant muscles. However, the results show a significant difference in Δ Oxy between paretic and non-paretic muscles, as well as a significant difference between normalized post-stroke and control data. Further work will be necessary to determine if the observed difference between the paretic and non-paretic muscles changes over the course of physical therapy and can be correlated with functional improvements.